Doping Dependent In‐Plane and Cross‐Plane Thermoelectric Performance of Thin n‐Type Polymer P(NDI2OD‐T2) Films. (25th May 2020) - Kluge, Regina M.; Saxena, Nitin; Chen, Wei; Körstgens, Volker; Schwartzkopf, Matthias; Zhong, Qi; Roth, Stephan V.; Müller‐Buschbaum, Peter
Abstract: Thermoelectric generators pose a promising approach in renewable energies as they can convert waste heat into electricity. In order to build high efficiency devices, suitable thermoelectric materials, both n‐ and p‐type, are needed. Here, the n‐type high‐mobility polymer poly[ N, N ′‐bis(2‐octyldodecyl)naphthalene‐1, 4, 5, 8‐bis(dicarboximide)‐2, 6‐diyl]‐alt‐5, 5′‐(2, 2′‐bithiophene) (P(NDI2OD‐T2)) is focused upon. Via solution doping with 4‐(1, 3‐dimethyl‐2, 3‐dihydro‐1H‐benzoimidazol‐2‐yl)‐ N, N ‐diphenylaniline (N‐DPBI), a maximum power factor of (1.84 ± 0.13) µW K −2 m −1 is achieved in an in‐plane geometry for 5 wt% dopant concentration. Additionally, UV–vis spectroscopy and grazing‐incidence wide‐angle X‐ray scattering are applied to elucidate the mechanisms of the doping process and to explain the discrepancy in thermoelectric performance depending on the charge carriers being either transported in‐plane or cross‐plane. Morphological changes are found such that the crystallites, built‐up by extended polymer chains interacting via lamellar and π–π stacking, re‐arrange from face‐ to edge‐on orientation upon doping. At high doping concentrations, dopant molecules disturb the crystallinity of the polymer, hindering charge transport and leading to a decreased power factor at high dopant concentrations. These observations explain why an intermediate doping concentration of N‐DPBI leads to an optimized thermoelectric performance of P(NDI2OD‐T2) in an in‐plane geometry as compared to the cross‐plane case. Abstract : Upon doping, the orientation of the flat plate‐like P(NDI2OD‐T2) crystallites, made up of lamellar and π–π stacking interactions between extended polymer chains, changes from the mainly face‐on to the edge‐on orientation, which explains the significantly improved in‐plane versus cross‐plane thermoelectric performance of the P(NDI2OD‐T2) films.